(untitled) (Research, Society and Development, 2023)
Objectives: To verify the behavior of cerebrovascular diseases in the city of São Paulo. Describe morbidity and mortality through hospital admission rates and mortality rates during 2019, 2020 and 2021. Methodology: the epidemiological study in question is cross-sectional, quantitative and observational, data were collected through the TABNET/DATASUS, an instrument that allows access to health information from the SUS. Data analysis was performed with arithmetic mean and representations in percentages. Results: It was possible to observe, based on data collected from DATASUS, that hospital admissions showed a numerical decline from 2019 to 2021, but, on the contrary, mortality rates increased from 2019 to 2021 when referring to cerebrovascular diseases. It is possible to observe that the month with the highest mortality rates due to cerebrovascular diseases in the three years was the month of May 2020. Conclusion of the study: There was a significant increase in mortality rates in the city of São Paulo, this fact may be associated with emerging evidence that the SARS-CoV-2 virus may cause neurological and thromboembolic complications, not only the longevity of the population.